2018
DOI: 10.1039/c8ra05545a
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm activity, ammonia removal and cell growth of the heterotrophic nitrifier,Acinetobactersp., facilitated by exogenousN-acyl-homoserine lactones

Abstract: In the present study, the heterotrophic nitrification–aerobic denitrification strain, Acinetobacter sp. JQ1004, was treated with three typical N-acyl-homoserine lactone (AHL) molecules (C6-HSL, C8-HSL, and 3-oxo-C10-HSL) during the nitrogen removal process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Zhang et al demonstrated that the addition of exogenous AHLs stimulated the sustained release of AHLs in a sequencing batch reactor. It has been shown that C6-HSL can increase the rate of ammonia and nitrate removal, PN concentration, and abundance of amoA , which was consistent with the fast COD and ammonia nitrogen removal rates observed in the bisynergistic-QS system groups in stage I in the present study. In stage II, C6-HSL, 3OC12-HSL, and 3OC14-HSL in R M3 were 1.78–2.98 folds, 1.21–1.69 folds, and 1.06–1.40 folds of those in R M1 and R M2 at day 34.…”
Section: Resultssupporting
confidence: 90%
“…Zhang et al demonstrated that the addition of exogenous AHLs stimulated the sustained release of AHLs in a sequencing batch reactor. It has been shown that C6-HSL can increase the rate of ammonia and nitrate removal, PN concentration, and abundance of amoA , which was consistent with the fast COD and ammonia nitrogen removal rates observed in the bisynergistic-QS system groups in stage I in the present study. In stage II, C6-HSL, 3OC12-HSL, and 3OC14-HSL in R M3 were 1.78–2.98 folds, 1.21–1.69 folds, and 1.06–1.40 folds of those in R M1 and R M2 at day 34.…”
Section: Resultssupporting
confidence: 90%
“…Figure 11 shows the cultures in a semi-continuous process with an agitation of 120 rpm to guarantee no limitations in the oxygen supplies. The immobilized bacteria culture showed, at the final stage of the process, an increment of the nitrification performance which is probably due to the biofilm maturity of the bacterial consortium [57,58]. One of the most striking features is the performance of modelization applied on real wastewater in a large period of time.…”
Section: Inhibition Assays: Maximum Load Of Brnwmentioning
confidence: 99%
“…Laser scanning confocal microscopy (LSCM) is often used to observe biofilm formation in a QS enhancement system, but rarely giving quantitative results. We collected the LSCM images from some researches and calculated the pixels proportion of fluorescent biofilm with and without QS enhancement (Huang et al, 2016;Hu et al, 2017;Wang et al, 2018;Xiong et al, 2020). The result is shown in Fig.…”
Section: Biofilm Formationmentioning
confidence: 99%
“…However, the positive effect of QS enhancement for other QS signaling molecule content such as PQS and AIPs on EPS production is lack solid evidence. There are some QS signaling molecule such as diffusible signal factor (DSF), 3OC6-HSL, 3-oxo-C10-HSL might have no significant positive or negative effect on EPS production in biological treatment systems (Ding et al, 2015;Lv et al, 2018;Wang et al, 2018;Huang et al, 2019), and the reason why those QS signaling molecule had opposite EPS trends with increasing their content s in bioreactors is still not understood. These molecules should be avoided in similar conditions if the aim is to increase the EPS production.…”
Section: Eps Productionmentioning
confidence: 99%